ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH PROVINSI DI INDONESIA - Ririn Hendriyani; Afrizal Tahar (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
This study is aimed to analyze the factors affecting the level of disclosure in the financial statements of the provincial governments in Indonesia. The subjects in this study are the Summary of Financial Statements Examination Results of Provincial Governments in Indonesia conducted by the Supreme Audit Agency (BPK). In this study, the sample included 30 provinces with a 3-year reporting period. Samples were selected using purposive sampling method. The analytical tool used is multiple regression analysis. Based on the analysis that has been done, it shows that the capital expenditure and number of population give significant positive effects on the level of disclosure in the financial statements of the provincial governments in Indonesia.Keywords: level of disclosure, level of dependence, Locally-Generated Revenue, capital expenditures, population, audit findings, government accounting.